Aproveitamento da torta residual proveniente da extração do óleo da amêndoa de macaúba (Acrocomia aculeata) para produção de farinha destinada à alimentação humana - Ana Luiza Machado Silveira (2014)
Nowadays the sustainable exploitation of the many resources in Brazil brought a new kind of palm tree to be studied by the Brazilian scientist community due to its presence in great part of the territory: the Macaúba (Acrocomia aculeata). Producer co-operative and small factories are the mainly vendors of Macaúba and they use their life experience in the rural community to get the oil present in the fruit and then use it to produce aliments and soap. However, mainly in the State of Minas Gerais, the significant presence of natural massive and the high productivity in oils of the fruit have led to the development of researches of the integral use of all parts of the Macaúba on several sections as food, cosmetic, pharmacy and energy industries. The quantity of oil in the fruit reaches until 20% in mass of fresh fruit, being got from pulp that is composed majority by unsaturated fatty acid, oleic type or from the kernel that is composed majority by saturated fatty acid, lauric type. The co-products from the pulp and kernel oil extraction are the cakes that can be used in the food industries due to their nutritional and sensory characteristics. The aim of this work is to process the kernel to obtain oil and cake. In the analysis of the extraction process by press it was evaluated the efficiency in function of the reduction of kernel size. The results demonstrated that the reduction in size of 1.60 mm or smaller is not efficient once that there wasnt an increase of oil extraction. Hence, the use of kernels with several sizes resulted by the process of separation of kernel from cored throughout the crusher is the recommended. The paper work includes the results from the characterization of the oil related to the quality parameters and lipid structure, as well as the evaluation of the cake throughout the analysis of centesimal compounds. Kernel oil showed to be resistant to deterioration, keeping a low acidity and moisture, and peroxide test negative. The kernel cake characterization showed high values to proteins (17.73%), fibers (41.48%) and lipids (47.35%) and low moisture content (6.32%), proving its nutritive value and the possibility of use in food. The ending focus of this work is the use of the kernel cake to produce cookies. Three different formulas for cookie production were developed, with respective wheat flour replacement levels of 0%, 30% and 60%. The results of sensory analysis indicate that the application of this cake is positive, presenting good averages in the Acceptance Tests for the levels of 30% and 60% replacement. Yet, it is important to remind that its low cost and facility of processing make this way of use to be very accessible to small producers.